2013
DOI: 10.1002/elps.201300491
|View full text |Cite
|
Sign up to set email alerts
|

CE with chemiluminescence detection for the determination of thyroxine in human serum

Abstract: A sensitive and rapid approach to perform thyroxine (T4) assay by CE with chemiluminescence (CL) detection was developed. The sensitive detection was based on the enhancement effect of T4 on the CL reaction between luminol and potassium permanganate (KMnO4 ) in alkaline solution. A laboratory-built reaction flow cell and a photon counter were deployed for the CL detection. Experimental conditions for CL detection were studied in detail to achieve maximum assay sensitivity. Optimal conditions were found to be 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Li et al. employed CE‐UV to measure six thyroid hormones in human serum samples following preanalysis treatment of the serum by ion pair hollow fiber liquid‐liquid‐liquid micro‐extraction. Employing this technique the authors could separate diiodothyronine, 3,3,5‐triiodo‐l‐thyronine, 3,5,3,5‐tetraiodolthyronine, 3,3,5‐triiodothyronine, monoiodotyrosine, and diiodotyrosine in 13 min using 20 kV and a BGE of 25 mM phosphate buffer, pH 2.5 plus 10% v/v acetonitrile and 0.5% m/v polyethylene glycol.…”
Section: Applications In Different Clinical Fieldsmentioning
confidence: 99%
“…Li et al. employed CE‐UV to measure six thyroid hormones in human serum samples following preanalysis treatment of the serum by ion pair hollow fiber liquid‐liquid‐liquid micro‐extraction. Employing this technique the authors could separate diiodothyronine, 3,3,5‐triiodo‐l‐thyronine, 3,5,3,5‐tetraiodolthyronine, 3,3,5‐triiodothyronine, monoiodotyrosine, and diiodotyrosine in 13 min using 20 kV and a BGE of 25 mM phosphate buffer, pH 2.5 plus 10% v/v acetonitrile and 0.5% m/v polyethylene glycol.…”
Section: Applications In Different Clinical Fieldsmentioning
confidence: 99%
“…Mu et al. also described a sensitive and rapid approach to perform thyroxine assay by CE–CL detection, which was based on the enhancement effect of thyroxine on the CL reaction between luminol and potassium permanganate in alkaline solution. A lab‐built reaction flow cell and a photon counter were deployed for the CL detection.…”
Section: Applicationsmentioning
confidence: 99%
“…In some cases, the analytes were labeled by CL reagents such as N ‐(4‐aminobutyl)‐ N ‐ethylisoluminol (ABEI) for CE–CL detection. Table shows drug analysis by CE–CL system in recent decade.…”
Section: Applicationsmentioning
confidence: 99%
“…Literature can be found that reports on thyroid hormones (a small molecule type) in human or animal serum, urine, or tissues, either in its pure or synthetic form, by using sensors or methods that are the outcome of combining more than two techniques and at least one kind of antibody, all of them with the aim of contributing to the understanding of hypo-and hyperthyroidism. In that sense, a list of techniques includes chromatography coupled with mass spectroscopy [10][11][12][13][14][15], immunoassays with magnetic or plasmonic nanoparticles [16][17][18], electrochemical or chemiluminescence techniques complemented with immunoassays and/or nanoparticles [19][20][21][22][23][24], among others. Some of those techniques require pretreatment, purification, or labeling of the sample, while others use high-pressure conditions, which generate an increase in the analysis costs [10,12,13,16].…”
Section: Introductionmentioning
confidence: 99%